Determination of Optimal Fermentation Condition for N-acetylglucosamine Production Using Mucor circinelloides Extracellular Chitinase - Yuniwaty Halim; Hardoko Hardoko; Reinald Febryanto Pengalila (Jurnal Perikanan Universitas Gadjah Mada, 2019)
This research aimed to determine the best fermentation condition, consists of pH, temperature, fermentation time and substrate concentration, in N-acetylglucosamine production from shrimp shells using crude extracellular chitinase obtained from Mucor circinelloides mould. The method used was experimental method with fermentation treatment of different pH (5, 6, 7, 8 and 9) and temperature (30, 40, 50, 60, 70 and 80°C). The optimal pH and temperature of fermentation obtained was used to determine the maximum substrate concentration (0.5, 1, 1.5 and 2%) and fermentation time (2, 4, 6 and 24 hours) to produce the highest concentration of N-acetylglucosamine. The optimal pH for fermentation was 8, with chitinase activity of 4.38±0.06 U/ml, while the optimal temperature was 50°C with enzyme activity of 5.42±0.06 U/ml. Substrate concentration and fermentation time affected the N-acetylglucosamine production. The optimal fermentation condition was obtained with substrate concentration of 1.5% and fermentation time of 2 hours resulted to N-acetyl Glucosamine concentration of 2195.83±15.14 ppm.